Frederick E. Terman and the rise of Silicon Valley. (1st January 1998) - Williams, James C.
It was Frederick E. Terman's vision and life's work which created the foundation for Silicon Valley. Local experience of interaction between industry and university in the field of electrical engineering, dating from the 1880s, and wireless communication, dating from the 1910s, was harnessed by Terman to promote the interests of the Stanford University. As director of the Applied Electronics Laboratory, Terman reinforced the relations between university and industry, by selecting only projects which would strengthen Stanford's basic electronics research and enhance the university's reputation. Backed by Varian Associates, Terman transformed the initial plans for a Stanford housing and industrial site into the backbone of what today is Silicon Valley, with companies such as Fairchild and Lockheed.